Recommended Reads - Multimodal Texts to Facilitate In-Depth English Learning - Alyssa Lowery (CLELEjournal, 2024)
Introduced by Alyssa Lowery, the Recommended Reads spotlight four multimodal texts that could facilitate in-depth English learning and encourage responding creatively to engaging stories.